1987
DOI: 10.1128/mcb.7.2.718
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hamster P-glycoprotein and multidrug resistance in DNA-mediated transformants of mouse LTA cells.

Abstract: The overexpression of a plasma membrane glycoprotein, P-glycoprotein, is strongly correlated with the expression of multidrug resistance. This phenotype (frequently observed in cell lines selected for resistance to a single drug) is characterized by cross resistance to many drugs, some of which are used in cancer chemotherapy. In the present study we showed that DNA-mediated transformants of mouse LTA cells with DNA from multidrug-resistant hamster cells acquired the multidrug resistance phenotype, that the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although mammalian P glycoproteins have been expressed in cDNA transfected cells, some of the results obtained studying those transfected cells are difficult to interpret due to the experimental protocol involved. One important point is that after the transfection step the cells must undergo at least two rounds of selection in the presence of drugs to be isolated as transfectants (24)(25)(26)(27)(28)(29). This is related to the low level of resistance shown by the transfected cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mammalian P glycoproteins have been expressed in cDNA transfected cells, some of the results obtained studying those transfected cells are difficult to interpret due to the experimental protocol involved. One important point is that after the transfection step the cells must undergo at least two rounds of selection in the presence of drugs to be isolated as transfectants (24)(25)(26)(27)(28)(29). This is related to the low level of resistance shown by the transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…These and additional observations (15)(16)(17)(18)(19)(20) have led to the hypothesis that the P glycoprotein acts as an energy-dependent drug-effiux pump and functions directly as a multidrug transporter in MDR cells. In fact, cDNA and genomic transfection experiments have provided evidence indicating that increased expression of the human, hamster, and mouse P glycoprotein can mediate the MDR phenotype (21)(22)(23)(24)(25)(26)(27)(28)(29). Interestingly, these studies have shown that the transfection of a single member of the P glycoprotein gene family results in the transfer of a variable MDR phenotype to the recipient drug-sensitive cells.…”
mentioning
confidence: 99%
“…In each case the transfer ofthe multidrug-resistant phenotype was correlated with the transfer of multiple copies of the DNA from the donor cell line, which hybridized to the cloned mdr P-glycoprotein sequences, and the overexpression of the 5-kb mRNA previously shown to be overexpressed in multidrug-resistant cell lines. Deuchars et al (28) were able to document that increased expression of P-glycoprotein was of donor origin using a species-specific MAb. Further, the P-glycoprotein sequences were transfected independently of the group of six genes previously shown to be coamplified in multidrug-resistant cell lines (21).…”
Section: Genetic Transfer Ofmultidrug Resistancementioning
confidence: 99%
“…Independent transformation experiments with DNA from multidrug-resistant human or hamster cell lines consistently show transfer of only a subset of the P-glycoprotein genespecific DNA restriction fragments (5,23). This finding suggests that only a single P-glycoprotein gene family member is transferred and amplified.…”
Section: Discussionmentioning
confidence: 93%